Transcriptome and histone epigenome of Plasmodium vivax salivary-gland sporozoites point to tight regulatory control and mechanisms for liver-stage differentiation in relapsing malaria. Issue 7 (June 2019) - ,; Muller, Ivo; Jex, Aaron R.; Kappe, Stefan H.I.; Mikolajczak, Sebastian A.; Sattabongkot, Jetsumon; Patrapuvich, Rapatbhorn; Lindner, Scott; Flannery, Erika L.; Koepfli, Cristian; Ansell, Brendan; Lerch, Anita; et al.
Graphical abstract: Highlights: Plasmodium vivax sporozoite transcriptome is heavily populated by transcripts that are highly abundant as mRNAs. RNA-binding proteins are highly transcribed in the sporozoite stage. Key examples of sporozoite-enriched RNA-binding proteins include several with homologs in other organisms. Many putatively repressed transcripts function in early infection and liver-stage development in the human host. Chromatin epigenetics presented here highlights the role of histone marks in transcriptional activity. Abstract: Plasmodium vivax is the key obstacle to malaria elimination in Asia and Latin America, largely attributed to its ability to form resilient hypnozoites (sleeper cells) in the host liver that escape treatment and cause relapsing infections. The decision to form hypnozoites is made early in the liver infection and may already be set in sporozoites prior to invasion. To better understand these early stages of infection, we undertook a comprehensive transcriptomic and histone epigenetic characterization of P. vivax sporozoites. Through comparisons with recently published proteomic data for the P. vivax sporozoite, our study found that although highly transcribed, transcripts associated with functions needed for early infection of the vertebrate host are not detectable as proteins and may be regulated through translational repression. We identified differential transcription between the sporozoite and published transcriptomes of asexual blood stages and mixed versus hypnozoite-enriched liver stages. These comparisons point to multiple layers of transcriptional, post-transcriptional and post-translational control that appear active in sporozoites and to a lesser extent hypnozoites, but are largely absent in replicating liver schizonts or mixed blood stages. We also characterised histone epigenetic modifications in the P. vivax sporozoite and explored their role in regulating transcription. Collectively, these data support the hypothesis that the sporozoite is a tightly programmed stage to infect the human host and identify mechanisms for hypnozoite formation that may be further explored in liver stage models.